2021
DOI: 10.20944/preprints202102.0103.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Composite Materials for Wear-Resistant Layers Made Using Electro-Spark Deposition

Abstract: This paper presents the results of the investigation of composite sinters W-TiB2 which were used as an electrode in the process of electro-spark deposition (ESD) and the examination of the deposited layers. The scope of the study includes detailed characteristics of powder mixtures, composite sinters made using the spark plasma sintering method (SPS) and layers deposited in the electro-spark process. The ESD process, using the W+30 vol.% TiB2 electrode, was carried out using an automated device. The substrates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The impact strength of a monolithic metal, which characterizes its resistance to dynamic destruction, depends on its chemical composition and structural state. As can be seen from Figure 1, for the compositions of the clad metal (1,3,4,5), the impact strength monotonically increases from 35Cr3W9 to 12Cr12Mn12SiV. The impact strength almost triples during the transition from the 35W9Cr3VSi composition with the structure of twinned martensite, carbide eutectic (large carbides located along the grain boundaries), and isolated low-strength ferrite sections to the 25Cr5VMoC composition with the structure of lath martensite and partial crystals of twinned martensite.…”
Section: Study Of Macrostructural Characteristics Of Monolithic Mater...mentioning
confidence: 92%
See 1 more Smart Citation
“…The impact strength of a monolithic metal, which characterizes its resistance to dynamic destruction, depends on its chemical composition and structural state. As can be seen from Figure 1, for the compositions of the clad metal (1,3,4,5), the impact strength monotonically increases from 35Cr3W9 to 12Cr12Mn12SiV. The impact strength almost triples during the transition from the 35W9Cr3VSi composition with the structure of twinned martensite, carbide eutectic (large carbides located along the grain boundaries), and isolated low-strength ferrite sections to the 25Cr5VMoC composition with the structure of lath martensite and partial crystals of twinned martensite.…”
Section: Study Of Macrostructural Characteristics Of Monolithic Mater...mentioning
confidence: 92%
“…The study [2] investigated the feasibility of using upward friction stir processing (UFSP) technology to create surface composites of dissimilar aluminum-based alloys that are reinforced with functional microparticles. Research findings reported in [3] indicate that electro-spark deposition (ESD) can be used to produce composite materials.…”
Section: Introductionmentioning
confidence: 99%